Investigating physiological responses and fine particulate matter retention of urban trees in Budapest - Haimei Chen; Levente Kardos; Haibin Chen; Veronika Szabó (City and Environment Interactions)
The urban environment is posing substantial challenges to both human well-being and the growth of plantations. Deploying advanced urban trees that effectively interact with atmospheric pollution will be a crucial step in urban planning. However, there is a paucity of knowledge in Hungary regarding these aspects. We studied the photosynthesis activities of three commonly planted trees (Acer platanoides, Fraxinus excelsior, and Tilia tomentosa) from two locations in Budapest, as well as their potential of capturing fine particulate matter on leaf surfaces. Our results reveal that T. tomentosa has developed a denser canopy and better photosynthetic activities, hence enhancing its adaptation to the urban environment in Budapest. F. excelsior showed a higher amount of fine PM wash-off, as it has a smoother leaf surface and was subjected to influences from wind speed and precipitation, making the captured particles more easily dislodged. Whereas fine PM concentration of A. platanoides and T. tomentosa were influenced by ambient PM10 and PM2.5, which might retain on their rough and hairy leaf surfaces. Approximately 38.17 tons of fine PM could be retained on urban greenery of Budapest at any given moment, highlighting the significant ecological and economic benefits of urban greenery. However, more accurate and long-term modeling is needed to develop a sustainable strategy for maximizing these benefits.